Sustainable biogenic synthesis of silver nanoparticles for oral cancer: a comprehensive review - Kumarasamy, Ranil Vikraman; Natarajan, Prabhu Manickam; Mathivanan, Isai; Balasubramaniam, Mohanapriya; SN, Suresh; Prabhu, Dhamodharan; Raju, Kamaraj; Mironescu, Monica; Mironescu, Ion Dan (Frontiers in Nanotechnology, 2026)
The increasing incidence of oral malignancies, coupled with the limitations of conventional treatments such as toxicity and drug resistance, has driven the exploration of novel therapeutic approaches. Silver nanoparticles (AgNPs) have emerged as promising anticancer agents due to their distinctive physicochemical attributes, which facilitate antimicrobial, anti-inflammatory, and tumor-suppressive activities. Unlike traditional chemical or physical synthesis methods, plant-mediated green synthesis offers a sustainable and ecologically sound alternative, leveraging the natural reducing and stabilizing compounds inherent in botanical extracts. This review provides a detailed analysis of contemporary advancements in the eco-conscious production of AgNPs using diverse plant sources and their potential role in addressing oral cancer. Furthermore, the article evaluates the cytotoxic impact of these biogenic nanoparticles on oral cancer cell models, elucidating molecular pathways such as oxidative stress induction, apoptosis activation, and inhibition of proliferative signaling. Clinical implications are explored, emphasizing the balance between therapeutic efficacy and biocompatibility in normal cells. While plant-derived AgNPs present a groundbreaking avenue for targeted oral cancer therapy, challenges such as scalability, standardization, and long-term safety require resolution for successful clinical translation. This synthesis of current knowledge aims to inspire innovative, nature-driven strategies to enhance oral oncology outcomes.